Catalytic and molecular properties of rabbit liver carboxylesterase acting on 1,8-cineole derivatives - Loandos, Maria del Huerto (2012)
Rabbit liver carboxylesterase (rCE) was evaluated as the catalyst for the enantioselective hydrolysis of (±)-3-endo-acetyloxy-1,8-cineole [(±)-4], which yields (1S,3S,4R)-(+)-3-acetyloxy-1,8-cineole [(+)-4] and (1R,3R,4S)-(-)-3-hydroxy-1,8-cineole [(-)-3]. Enantioselective asymmetrization of meso-3,5-diacetoxy- 1,8-cineol (5) gives (1S,3S,4R,5R)-(-)-3-acetyloxy-5- hydroxy-1,8-cineole (6), with high enantioselectivity. rCE has been chosen to perform both experiments and molecular modeling simulations. Docking simulations combined with molecular dynamics calculations were used to study rCE-catalyzed enantioselective hydrolysis of cineol derivatives. Both compounds were found to bind with their acetyl groups stabilized by hydrogen bond interactions between their oxygen atoms and Ser221.